2019
DOI: 10.1183/23120541.00065-2019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the diagnostic accuracy of Xpert MTB/Rif assay and culture for pleural tuberculosis using tissue biopsy

Abstract: BackgroundEarly diagnosis of pleural tuberculosis is difficult as it is a paucibacillary disease and a combination of tests is required to diagnose it, which have varied diagnostic accuracy and increase the cost. The aim of this study was to evaluate the diagnostic performance of the Xpert MTB/Rif assay on thoracoscopic pleural biopsy specimens.MethodsA total of 201 patients with exudative pleural effusion and normal lung parenchyma were included in the study. All patients underwent thoracoscopic pleural biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…The reported sensitivity of PCR is highly heterogeneous, ranging between 45% and 100%, depending on the method of PCR assay, gold standards and method of biopsy. [9 - 11 , 20 - 22] The conventional PCR studies [20 22] reported higher sensitivity (56 - 100%) than the Xpert MTB/RIF assay studies (30 - 85%). [9 – 11] Most studies obtained pleural tissue by either computed tomography-guided biopsy [22] or thoracoscopic biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The reported sensitivity of PCR is highly heterogeneous, ranging between 45% and 100%, depending on the method of PCR assay, gold standards and method of biopsy. [9 - 11 , 20 - 22] The conventional PCR studies [20 22] reported higher sensitivity (56 - 100%) than the Xpert MTB/RIF assay studies (30 - 85%). [9 – 11] Most studies obtained pleural tissue by either computed tomography-guided biopsy [22] or thoracoscopic biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…[9 - 11 , 20 - 22] The conventional PCR studies [20 22] reported higher sensitivity (56 - 100%) than the Xpert MTB/RIF assay studies (30 - 85%). [9 – 11] Most studies obtained pleural tissue by either computed tomography-guided biopsy [22] or thoracoscopic biopsy. [10 , 11 , 20] Only one study obtained pleural tissue via closed pleural biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Definite discrimination between these 2 etiologies can be established only by PCR and culture. 11 12 Two patients with NTM granulomatous pleurisy were diagnosed by positive NTM culture in pleural tissue or fluid. These findings indicate that clinicians should actively make every effort to find microbiological evidence of potential pathogens in all available specimens, even in cases with granulomatous histological results.…”
mentioning
confidence: 99%